2018
DOI: 10.3390/ma11091536
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Enhancement of Thermal Conductivity and Dielectric Properties in Al2O3/BaTiO3/PP Composites

Abstract: Multifunctional polymer composites with both high dielectric constants and high thermal conductivity are urgently needed by high-temperature electronic devices and modern microelectromechanical systems. However, high heat-conduction capability or dielectric properties of polymer composites all depend on high-content loading of different functional thermal-conductive or high-dielectric ceramic fillers (every filler volume fraction ≥ 50%, i.e., ffiller ≥ 50%), and an overload of various fillers (fthermal-conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 57 publications
(80 reference statements)
3
16
0
Order By: Relevance
“…Ren et al [68] obtained the simultaneous enhancement on thermal and mechanical properties of PP composites by adding graphite platelets (GPs) and graphene sheets (GSs). Yao et al [69] to the pristine PP) was recorded. Cheewawuttipong et al [70] added BN and vaporgrown carbon fiber (VGCF) into the PP resin.…”
Section: Hybrid Materialsmentioning
confidence: 99%
“…Ren et al [68] obtained the simultaneous enhancement on thermal and mechanical properties of PP composites by adding graphite platelets (GPs) and graphene sheets (GSs). Yao et al [69] to the pristine PP) was recorded. Cheewawuttipong et al [70] added BN and vaporgrown carbon fiber (VGCF) into the PP resin.…”
Section: Hybrid Materialsmentioning
confidence: 99%
“…It is worth mentioning that the thermal conductivity of the MWCNTs foams is similar to their BT/MWCNTs counterparts due to the low volumetric percentage of BT (as the maximum BT volume percentage is about 2 vol.%). Previous studies have shown that a large loading fractions (above 20 vol.%) of BT is needed to obtain a significant increase in the thermal conductivity of polymer composites [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…showed that the addition of the thermally conducting filler Al 2 O 3 decreased the dielectric strength of Al 2 O 3 /BaTiO 3 /PP, while the addition of a high dielectric constant filler material increased the dielectric strength in Al 2 O 3 /BaTiO 3 /PP [35].…”
Section: Dielectric and Thermally Conducting Fillersmentioning
confidence: 99%
“…[19]. With the help of a small-size ferroelectric ceramic filler, the high dielectric constant is obtained [1,4,35]. Ceramic nanofillers with large aspect ratio are preferred to their spherical counterparts for the improvement of of nanocomposites [36].…”
Section: Filler Materialsmentioning
confidence: 99%